Dynamics of relative area of rat liver structures in early postnatal period in norm and after intrauterine effect of an antigen or glucocorticoids. - Voloshin, M. A.; Bohdanov, P. V. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Infectious diseases that can exacerbate normal pregnancy affect not only maternal health, but also the future baby. Most infectious agents, primarily TORCH-infections and of bacterial ones, are tropic to liver and biliary ductules epithelium and can be the reason of congenital hepatitis and defects. Objective. The objective of the research is to determine the peculiarities in dynamics of relative area of rat liver structures in early postnatal period in norm and after intrauterine effect of an antigen or glucocorticoids. Methods. Morphometric and statistic methods have been uses during the research. Results. It has been determined that intrauterine antigenic load results in growth of sinusoidal capillaries relative area during the first 24 hours of the postnatal life with further tendency to decreasing and repeated grown on the 21st day. The growth of liver trabecules area is registered on the 3rd day. The index returns to norm by the end of the first week of postnatal life. It should be mentioned that intrauterine antigen effect results in depression of liver hematopoiesis function. Conclusion. Thus, intrauterine antigenic load results in violation of liver hematopoietic function and affects liver acini formation. Antenatal effect of glucocorticoids causes changes in formation of connective tissue component of the liver.